1972
DOI: 10.1055/s-0028-1097093
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Antibodies After Long-Term Insulin Treatment in a Diabetic Child

Abstract: 224Short Communications 96% of the radioactivity in A could be precipitated by incubation with an excess of rabbit anti-glucagon serum and subsequent addition of ethanoCln a corresponding test without antiserum, 3-4% of the radioactivity was precipitated.The relative amounts of 125 1 in r, MIT and DIT were found to be 2.6, 97.2 and 0.3%, respectively. The corresponding vaiues for a material radioiodinated in the same way as the material applied on the column but only purified by a saltingout procedure, were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…There are some reports that an immune response to proglucagon may occur in both NOD mice, as shown here, and in T1D patients . Indeed, glucagon‐specific antibodies have been demonstrated in some patients with T1D .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…There are some reports that an immune response to proglucagon may occur in both NOD mice, as shown here, and in T1D patients . Indeed, glucagon‐specific antibodies have been demonstrated in some patients with T1D .…”
Section: Discussionsupporting
confidence: 66%
“…There are some reports that an immune response to proglucagon may occur in both NOD mice, as shown here, and in T1D patients . Indeed, glucagon‐specific antibodies have been demonstrated in some patients with T1D . Although attributed to ‘immunization’ by glucagon contaminants present in exogenously administered insulin, a spontaneous autoimmune response should also be considered in light of our findings in the NOD mouse.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…5 Stahl et al studied 72 sera from juvenile diabetics and found evidence of glucagon binding in only one specimen. 6 Cresto et al detected antibodies to glucagon in three of 85 insulin-requiring diabetics. 7 This combined experience gives a frequency of only 1.6% of insulin-requiring diabetic patients with antibodies to glucagon.…”
Section: Discussionmentioning
confidence: 99%